INFLUENCES OF PARENTS AND PEERS ON ADOLESCENT SMOKING INITIATION: FINDINGS FROM A LONGITUDINAL STUDY IN KOTA TINGGI DISTRICT, JOHOR, MALAYSIA - Hock, Lim Kuang; Li, Lim Hui; Mohd Ghazali, Sumarni; Ling, Cheong Yoon; Cheong, Kee Chee; Heng Pei Pei; Teh Chien Huey; Tan Cia Vei; Mohd Hazilas Mat Hashim; Cheah Yong Kang; Lim Jia Hui (Malaysian Journal of Public Health Medicine, 2021)
Studies have shown that parents and peers are among the dominant factors that contribute to smoking initiation among non-smoking adolescents. The paucity of this information in Malaysia warrants a longitudinal study to determine the actual factors associated smoking initiation. The study aims to address the gaps in our knowledge on the factors that associated with smoking initiation among non-smoking school-going adolescents. We carried out a longitudinal study among non-smoking secondary school-going adolescents in Kota Tinggi district, Johor. A representative sample of 1682 was selected via multi-stage sampling and respondents were followed-up for a period of one year. A pre-validated questionnaire was used to collect data from the selected respondents and multivariable logistic regression was employed to determine the factors associated with smoking initiation among non-smoking school-going adolescents. Approximately 1 in 10 non-smoking school-going adolescents-initiated smoking at the end of follow-up. Having peers and a father who smokes were significantly associated with smoking in univariate analysis, similarly, a relationship was also observed in multivariable analysis between parents who smoked with smoking initiation after the effect of other independent variables were controlled (Adjusted relative risk: 1.81, 95% CI 1.06-2.95). The study revealed that parental influence was more dominant than peer influence with regard to smoking initiation. Therefore, intervention programmes should involve parents/guardians to enhance their chances of success and reduce the incidence of smoking among non-smoking school-going adolescents.